2008
DOI: 10.1140/epjb/e2008-00333-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of stochastic resonance in the mating behavior of Nezara viridula (L.)

Abstract: We investigate the role of the noise in the mating behavior between individuals of Nezara viridula (L.), by analyzing the temporal and spectral features of the non-pulsed type female calling song emitted by single individuals. We have measured the threshold level for the signal detection, by performing experiments with the calling signal at different intensities and analyzing the insect response by directionality tests performed on a group of male individuals. By using a sub-threshold signal and an acoustic Ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…A positive effect of noise on signal detection in Mecopoda chirpers thus appears comparable with the phenomenon of stochastic resonance, which improves the detection of subthreshold fluctuating signals by adding a weak random noise (Wiesenfeld and Moss, 1995). Meanwhile, this mechanism was found in different sensory systems of various species including insects (Levin and Miller, 1996; Spezia et al, 2008), frogs (Bibikov, 2002), mammals (Frisina et al, 1996; Lewis and Henry, 1995; Henry, 1999) and humans (Zhang-Cai et al, 2004; Zeng et al, 2000). However, for two reasons we are not sure whether the phenomenon of enhanced detection of the signal due to background of the trill is identical to stochastic resonance.…”
Section: Discussionmentioning
confidence: 99%
“…A positive effect of noise on signal detection in Mecopoda chirpers thus appears comparable with the phenomenon of stochastic resonance, which improves the detection of subthreshold fluctuating signals by adding a weak random noise (Wiesenfeld and Moss, 1995). Meanwhile, this mechanism was found in different sensory systems of various species including insects (Levin and Miller, 1996; Spezia et al, 2008), frogs (Bibikov, 2002), mammals (Frisina et al, 1996; Lewis and Henry, 1995; Henry, 1999) and humans (Zhang-Cai et al, 2004; Zeng et al, 2000). However, for two reasons we are not sure whether the phenomenon of enhanced detection of the signal due to background of the trill is identical to stochastic resonance.…”
Section: Discussionmentioning
confidence: 99%
“…This disrupting effect on the males' orientation observed in E. heros and N. viridula appears to be efficient only when background noise is in the narrow frequency range characteristic of stink bug communication signals. White noise amplified, by stochastic resonance, N. viridula females' signals and enabled communication even when signals were at subthreshold levels (Spezia et al 2008). Place of copulation of mates (male and female) placed in different plants that were maintained in physical contact.…”
Section: Discussionmentioning
confidence: 99%
“…N. viridula males reduced their signaling activity and did not start searching for the female when they were simultaneously stimulated with conspecific or heterospecific female calling signals (Miklas et al 2003) or natural and synthesized conspecific female calling signals with altered frequencies and temporal parameters (de Groot et al 2010;Žunič et al 2011). In contrast, Spezia et al (2008) showed that white noise improved the communication of N. viridula males on artificial dummy plants because signals at levels below the threshold of the insect's detection (subthreshold) were amplified by stochastic resonance phenomena.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 98%
“…In the last decade an increasing interest has been devoted towards possible constructive aspects of noise and fluctuations in physical and biological systems [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Previous studies have shown that, under specific conditions, an external noise can constructivelly interact with an intrinsically nonlinear system, characterized by the presence of intrinsic noise, giving rise to positive effects [13][14][15] such as stochastic resonance (SR) [16][17][18][19], resonant activation (RA) [20,21] and noise enhanced stability (NES) [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that, under specific conditions, an external noise can constructivelly interact with an intrinsically nonlinear system, characterized by the presence of intrinsic noise, giving rise to positive effects [13][14][15] such as stochastic resonance (SR) [16][17][18][19], resonant activation (RA) [20,21] and noise enhanced stability (NES) [22][23][24][25][26]. In particular, the possibility to suppress the intrinsic noise in n-type GaAs and Si bulk, driven by a static electric field, with the addition of a Gaussian correlated noise source, has been theoretically investigated [27].…”
Section: Introductionmentioning
confidence: 99%